PELATIHAN MENULIS BUKU BAGI GURU DI DIKDASMEN MUHAMMADIYAH RAWAMANGUN - Sugiarto Sutomo; Dimas Kurnia Robby; Unifah Rosyidi; Muhammad Ragil Firdaus; Ajeng Salissa Salsabila (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
The growing world of education requires skilled teachers to be able to keep up with the advancement of information technology in the world of education itself, the community service that we carry out focuses on providing training in the form of the ability for teachers to be able to improve the abilities and skills of teachers, especially in the field of authorship, which in this case we provide opportunities for teachers to be trained in writing for approximately 3 days and will directly through the editing process and in the end the results of the book work from the teachers have been published. We base this training that by writing it will create an academic ability, transmission in terms of teacher competence to readers, and in the end there is continuity in the science of each educator.